2013
DOI: 10.1002/cmdc.201300271
|View full text |Cite
|
Sign up to set email alerts
|

In silico Optimization of a Fragment‐Based Hit Yields Biologically Active, High‐Efficiency Inhibitors for Glutamate Racemase

Abstract: A novel lead compound for inhibition of the antibacterial drug target, glutamate racemase, is optimized for both ligand efficiency and lipophilic efficiency. A previously developed hybrid MD-docking and scoring scheme, FERM-SMD, is utilized to predict relative potencies of potential derivatives prior to chemical synthesis. This scheme was successful in distinguishing between high and low affinity binders with minimal experimental structural information, saving time and resources in the process. In vitro potenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…To explore the drugability of the Bc GR enzyme, a series of compounds (1H-benzimidazole-2-sulfonic acid, dipicolinic acid, 4-hydroxybenzene-1,3-disulfonate, and (2R)-2-amino-4-benzylpentanedioic acid) [24, 45, 46] which are already known inhibitors of different bacterial glutamate racemases, were screened for the inhibition of the enzymatic activity. Among all compounds tested, only dipicolinic acid was found to be a very weak inhibitor of Bc GR, showing an IC 50 value of 0.15 ± 0.03 mM (S3 Fig).…”
Section: Resultsmentioning
confidence: 99%
“…To explore the drugability of the Bc GR enzyme, a series of compounds (1H-benzimidazole-2-sulfonic acid, dipicolinic acid, 4-hydroxybenzene-1,3-disulfonate, and (2R)-2-amino-4-benzylpentanedioic acid) [24, 45, 46] which are already known inhibitors of different bacterial glutamate racemases, were screened for the inhibition of the enzymatic activity. Among all compounds tested, only dipicolinic acid was found to be a very weak inhibitor of Bc GR, showing an IC 50 value of 0.15 ± 0.03 mM (S3 Fig).…”
Section: Resultsmentioning
confidence: 99%
“…Primarily, two strategies for developing GR inhibitors have been described. First, a variety of Glu analogs have been successfully developed as inhibitors , and second, inhibitors that bind at allosteric sites have been discovered . Because of the importance of GR as an antibacterial target, the development of alternative inhibition strategies remains an important goal.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, we believed that, given the current apo-structure and our HTS hits, particularly, ‘ 1 ’ and ‘ 6 ’, that we could employ various integrated docking and molecular dynamics strategies to inevitably determine the locus and orientation of these RAD52-ssDNA inhibitors. An increasing body of literature has shown that when docking and MD are employed together that meaningful binding affinity rank ordering can be made, and that the many complex roles of water can often be inferred from these simulations (Whalen et al, 2011, Whalen et al, 2013). …”
Section: Using Docking and Molecular Dynamics Simulations To Make mentioning
confidence: 99%
“…This is largely because, although it employs MD simulations of the protein-ligand complex, it still relies in part on docking; for classic drug like compounds this should not be a problem, but for large macrocycles it would fail to capture true breadth their solution conformational ensembles. One possible solution to this is to use a free energy calculation that is amenable to medium throughput analysis, such as Extended Linear Response (ELR), which has been highly successful in explicitly capturing the contributions of interstitial waters to ligand binding (Whalen et al, 2013). …”
Section: Implications For Employing Roc and Md-informed Workflows mentioning
confidence: 99%